The efficiency of executing technical actions in volleyball and the teams` gender and sports level - Cieminski, K. (Trends in Sport Sciences, 2018)
Modern statistical methods related to team games can be very helpful in improving the quality of analysis. Aim of Study. The aim of the paper was to identify differences in the efficiency of executing technical actions by teams participating in the Men`s and Women`s European Volleyball Championship in 2013-2017, with consideration for the gender and the place taken in the final classification. Material and Methods. The research material consisted of teams (n = 96) divided into five groups: 1 - places 1-4, 2 - places 5-8, 3 - places 9-12, 4 - places 13--16, 5 - all teams. The results of efficiency in the serve, reception, setting the reception, the attack and the block were analysed. Results. Female teams were more efficient than the male ones in reception by 4.45% (p < 0.05) and in the block by 0.32 point(p < 0.05), while the male teams were better than the female ones in setting by 10.24% (p < 0.001) and in the attack by 7.46% (p < 0.001). Female teams from places 1-4 were more efficient in the serve by 0.44 point (p < 0.01), in setting by 13.93% (p < 0.001), in the attack by 9.00% (p < 0.001) and in the block by 1.00 point (p < 0.01) in comparison with teams from places 13-16. Similar results were obtained by men: in the serve by 0.44 point (p < 0.01), in setting by 13.93% (p < 0.001), in the attack by 9.00% (p < 0.001)and in the block by 1.00 point (p < 0.01). Conclusions. The obtained results indicate differences between male and female volleyball players. This necessitates using different methods of training. The efficiency of performing technical actions differentiates between teams from places 1-4 and 13-16. Therefore, in training control, coaches should primarily focus on tools that allow an assessment of the efficiency of male and female players in individual technical elements